The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/adts.202100208
|View full text |Cite
|
Sign up to set email alerts
|

Device Simulation of Ag2SrSnS4 and Ag2SrSnSe4 Based Thin‐Film Solar Cells from Scratch

Abstract: The structural, optoelectronic and elastic properties of quaternary chalcogenide materials Ag 2 SrSn(S/Se) 4 in kesterite (Kes) and stannite (Sta) phases are studied using the HSE hybrid functional within the density functional theory. Ag 2 SrSnSe 4 in kesterite and stannite phases is found to have direct bandgap of 1.13 and 1.38 eV, respectively, along the high symmetry 𝚪 points. To analyze the electronic properties, PDOS for Ag 2 SrSn(S/Se) 4 in kesterite and stannite phases are studied and explained. To ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In order to optimize the device entirely, we have also observed the capacitance-frequency (C-f) characteristics of the proposed PSC structure and the simulated C-f curves are illustrated in Figure 9. The characteristics of capacitance as a function of frequency are measured under zero-bias condition and at an operating temperature of 300 K. [65][66][67]69] The capacitance value is sufficiently low at the frequency below 10 7 Hz, as shown in Figure 9. However, the capacitance increases rapidly beyond 10 7 Hz, and the maximum capacitance is observed in the frequency ranged from 10 7 to 10 11 Hz.…”
Section: C-v and C-f Characteristics Of Perovskite Solar Cellmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to optimize the device entirely, we have also observed the capacitance-frequency (C-f) characteristics of the proposed PSC structure and the simulated C-f curves are illustrated in Figure 9. The characteristics of capacitance as a function of frequency are measured under zero-bias condition and at an operating temperature of 300 K. [65][66][67]69] The capacitance value is sufficiently low at the frequency below 10 7 Hz, as shown in Figure 9. However, the capacitance increases rapidly beyond 10 7 Hz, and the maximum capacitance is observed in the frequency ranged from 10 7 to 10 11 Hz.…”
Section: C-v and C-f Characteristics Of Perovskite Solar Cellmentioning
confidence: 99%
“…The horizontal axis intercept typically corresponds to the V bi of organic semiconductor devices, and the slope of 1/C 2 (V) in the MS plot is interpreted as a density of engaged trapping centers. [64][65][66][67] 8a indicates that the capacitance rises gradually as the applied voltage increases. It is observed that there is a less significant change in the capacitance with the ETL donor density.…”
Section: C-v and C-f Characteristics Of Perovskite Solar Cellmentioning
confidence: 99%
See 1 more Smart Citation